COVID-19: Knowledge, Attitude, Practice in Malaysia - Rafidah, Elias; Girthanah, Vigayan; Hamsaa Varrthini, Mohana Kumar; Mauna Sree, Sevanesan; Ragavinotini, Rajan; Savitha, Gurumoorthy (IJCRR, 2021)
Background: Malaysia is no exception to the COVID-19 pandemic, and to date, there is no specific treatment to cure the disease, and the vaccine is still not available. Hence, to stress the importance of practising protective measures. Objective: This study intended to examine the knowledge, attitude, and practice towards COVID-19 and its preventive measures among Malaysian amid the CMCO (Conditional Movement Control Order) during the COVID-19 pandemic in Malaysia. Methods: This cross-sectional study was conducted online among Malaysians aged 18 years old and above from May to June 2020 using a self-developed questionnaire through snowball sampling. Results: A total of 571 respondents were analyzed. The average age was 26 years old, and monthly income was RM1500, about half were females (57.8%), had education level to undergraduate (58.1%), one-third were Indians (34.7%), one-fifth were Malays (23.6%), one-third from Sarawak (31.2%), and one-fifth from Selangor (25.0 %). The correct rate for all three outcome domains was high, 83% for knowledge, 85% for attitude, and 86% for practice. Few respondents still holding the myths regarding COVID-19. No significant factors contributed to the knowledge score. Factors that contributed to higher attitude scores were monthly income and employment status. Factors that contributed to higher practice scores were female, Chinese, and medical employees. The higher the knowledge score, the higher the attitude score and practice score. Conclusions: Malaysians discerned and optimistic about COVID-19, its preventive measures, and the implementation of MCO. They had confidence with the government in combating COVID-19 and were practising preventive measures. Key Words: Attitude, COVID-19, Knowledge, Malaysia, Practice